2014
DOI: 10.1177/2278533720140205
|View full text |Cite
|
Sign up to set email alerts
|

Using Performance Appraisal as an Effective Tool for Motivating the Employees Performance: A Live Study

Abstract: The study aims to find the impact of perceived fairness of performance appraisal on employee performance in telecom sector. The study is based on descriptive research. Data was collected from the respondents through a standardized questionnaire. Sample Unit consisted of 80 employees from Vodafone and Tata Docomo. Statistical analysis of the quantified data was done using SPSS software. The analysis of responses was done by using correlation and regression analysis. According to Correlation analysis there exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…The study concluded that the employees were not fully satisfied by the separation of the training program into two parts, on the job and off the job training, but if sufficient data would have been provided to the employees in advance, this could have helped them during the training process. Kumari (2014) the study concluded that there exists a relationship between perceived fairness of performance appraisal and employee performance. The aftereffect of the measurable investigation was that there exists a huge effect of apparent reasonableness of execution evaluation on worker execution.…”
Section: The Discoveries Proposed That There Was An Essentialness Conmentioning
confidence: 92%
“…The study concluded that the employees were not fully satisfied by the separation of the training program into two parts, on the job and off the job training, but if sufficient data would have been provided to the employees in advance, this could have helped them during the training process. Kumari (2014) the study concluded that there exists a relationship between perceived fairness of performance appraisal and employee performance. The aftereffect of the measurable investigation was that there exists a huge effect of apparent reasonableness of execution evaluation on worker execution.…”
Section: The Discoveries Proposed That There Was An Essentialness Conmentioning
confidence: 92%
“…The level of an organization attainment of its goals and objectives are directly linked to the level of motivation the employee has Mwakindimi (2018). Research findings by Swank & Kamphorst (2015), Kumari (2014), Ushus & Johnson (2015), Akpotu & Oghvubu (2014), Suresh (2013) and Muhammad ,et.al (2011) all support a strong existing relationship between performance appraisal and motivation which leads to a positive outcome in the teaching and learning process. However Guarjardo 2011) opines that it is not automatic that PA appraisal will definitely lead to motivation of employees.…”
Section: Research Problemmentioning
confidence: 95%
“…The justifications for chosen this design are as follows: Firstly, the study population is relatively very large (employees of public sector in Ghana) and therefore more appropriate to employ survey design since it is considered as the best design gather authentic data to characterize a population too sizable to account for directly. (Babbie, 2013;Neuman, 2013). This design was applied in this study by designing questionnaire so as to collect data from the sampled population to support the design (Blaikie, 2010;Cohen et al, 2011;De Vaus, 2014;Morgeson et al, 2013.…”
Section: Methodsmentioning
confidence: 99%